Autoantibodies to alpha-synuclein in inherited Parkinson’s disease - Papachroni, Katerina K. (2007)
Neurodegeneration in Parkinson’s disease (PD) is accompanied by a local immune reaction in the affected brain regions. It is well established that α-synuclein is directly implicated in the pathogenesis of PD. Development of the disease is often associated with changes of expression and cellular compartmentalisation of this protein; moreover, its oligomers or protofibrils are often released to the CSF and plasma of patients. Aggregated α-synuclein can trigger the activation of microglia; however, its capacity to induce production of specific autoantibodies (AAb) has not been assessed. In this study, we examined the presence of AAb against synuclein family members in the peripheral blood serum of PD patients and control individuals. Presence of AAb against β-synuclein or γ-synuclein showed no association with PD. Multi-epitopic AAb against α-synuclein were detected in 65% of all patients tested and their presence strongly correlated with an inherited mode of the disease but not with other disease-related factors. The frequency of the presence of AAb in the studied group of patients with sporadic form of PD was not significantly different from the frequency in the control group but very high proportion (90%) of patients with familial form of the disease were positive for AAb against α-synuclein. We hypothesise that these AAb could be involved in pathogenesis of the inherited form of PD.